Pengaruh Green Accounting dan Dampak Lingkungan terhadap Keberlanjutan Operasional pada Perusahaan Manufaktur - Octavia Dwi Sagita Sari; Putri Nadiya Puspitasari; Imeltiana Imeltiana; Maria Yovita R Pandin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the influence of green accounting and environmental impact on the operational sustainability of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The method used is a quantitative method with data processing using SPSS. The study population includes 30 manufacturing companies listed on the IDX. The results of this study are that the green accounting variable has a significant influence on operational sustainability, while the environmental impact variable has a significant effect on sustainability. The green accounting and environmental impact variables have a significant effect simultaneously on operational sustainability.